(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2008)
Considering that one of the main behavior therapy purpose is to promote the client’s self-knowledge, the objective of this study was to analyse the verbal responses of an adult client categorized as “interpretative” in the clinical context according to the definitions of a previous study. The method consisted of the analysis and classification of 14 therapeutic sessions. The results showed the occurrence of the following categories in the client’s verbal repertoire: Information, Investigation, Interpretation and Consequencing. It was also found that: a) interpretations occurred in 74,88% of the client’s verbal episodes; b) the client interpreted with the function of explaining something in 78,00% of the interpretations and c) the client focused her own behavior in 73,20% of the interpretations. Such results seem to confirm the hypothesis of that the therapeutical setting is an environment in which the emission of interpretations is favored, thus contributing to the client´s self-knowledge.